PENINGKATAN PERCAYA DIRI MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS PESERTA DIDIK KELAS IV SDN 1 DONOTIRTO - Larasati , Esthi (Jurnal PGSD Indonesia, 2023)
The problem in this study is that it was found that most of the students at grade IV when studying Social Sciences still lacked confidence. This research aims at improving self-confidence through “problem based learning”. This confidence is important because with confidence students can follow the learning well, students will be able to master certain fields and easily absorb things that are informed. The type of this research was classroom action research (CAR). The subject were students at grade IV. The data analysis techniques were quantitative and qualitative descriptive. The results of the research show that the implementation of “problem based learning” can improve student’s self-confidence. The average score of students’ self confidence before the action was 37.75 with 3 students or 12.5% classified as ≥ highly confident. It increased to 46.58 with 12 students or 50.00% classified as ≥ highly confident in cycle I and increased again to 50.08 with 21 students or 87.50% classified as ≥ highly confident in cycle II. Based on the results of the study it can be concluded that the “problem-based learning” model can increase students' self-confidence in social studies learning at grade IV SDN 1 Donotirto